Coating of Tin Octoate on Ceramic Support: Effect of Polyvinyl Alcohol and Polyethylene Glycol as Binders - Ibrahim, Norliza; Muiz Abdul Jalil, Abdul; Muzzamil Asyraf Musa, Muhammad; Nadzirah Suhaidi, Amira (International Journal of Engineering and Technology, 2018)
It has been an interest to produce immobilized tin (II) octoate catalyst on the surface of the ceramic support for the production of polylactic acid (PLA) from lactic acid (LA) due to ease of recycling and separating the catalyst. The objectives of this study are to produce ceramic support coating using polyethylene glycol (PEG) and polyvinyl alcohol (PVA) binders and to characterize the tin (II) octoate coating using EDX and standard adhesion test. Ceramic powder was obtained from ceramic waste and used to make the support by mixing with diluted PVA in a ratio of 3:1 before compressing and sintering in furnace at 1100oC. Then, a thin layer of tin (II) octoate was prepared using nitric acid, ethylene glycol (EG) and different types of binders. Dip coating technique was used to coat the thin layer on the ceramic surface before sintering in an oven. Based on the EDX result, the composition of tin present in the thin layer containing PEG binder is 5.50 % compared to only 0.46 % of that containing PVA binder. In addition, result from adhesion test showed that the thin layer sample containing PEG did not peel off from the ceramic surface, while the thin layer containing PVA stuck to the tape and peeled off from the surface of ceramic at 37.5 %. In conclusion, PEG binder was recommended for the immobilization of high composition of tin (II) octoate on the ceramic surface.Â Â